P-D2 Macrophage Autophagy Facilitates Sustained Release of Nanoformulated Antiretroviral Drugs From Autophagosomal Depots Enhances Anti-HIV-1 Activities. (March 2017) - Gnanadhas, Divya Prakash; Dash, Prasanta; Silman, Brady; Lin, Zhiyi; Bade, Aditya; Gelbard, Harris; Mcmillan, Joellyn; Edagwa, Benson; Gendelman, Howard; Gorantla, Santhi
Abstract : The realization that long-acting nanoformulated antiretroviral therapy (ART) can be broadly made available for clinical care is stymied by the few drugs available. Thus, there is an immediate need to develop sustained release anti-HIV products with a dosing interval measured in months. This would overcome inherent therapeutic challenges of drug adherence, biodistribution and long-term toxicities. We previously demonstrated that this goal could be realized by producing hydrophobic nanoformulated ART (nanoART) with particle sequestration in macrophage endosomes. This may be made possible through the actions of the mixed lineage kinase inhibitor, URMC-099. The drug facilitates reductions in viral load and protects CD4+ T lymphocytes in infected humanized mice. We now report that URMC-099's action is, in part, through the stimulation of autophagy. URMC-099 reduces JNK phosphorylation leading to modulation of mTORC1, which in turn, controls vesicular trafficking through transcription factor EB (TFEB). TFEB affects antiretroviral drug (ARV) nanoparticle depots and drug-particle dissociations. Human monocyte-derived macrophages given both nanoformulated atazanavir (nanoATV) and URMC-099 then infected with HIV-1ADA show TFEB nuclear translocation and mTORC1 inhibition. Parallel upregulation of LC3B, BECN1 and SQSTM1 are observed. URMC-099 increases nanoATV levels in autophagosomes for a range of antiretroviral concentrations with improvements in mitochondrial activity and pharmacokinetic profiles. This leads to improved viral clearance and are operative for both ATV and dolutegravir. As treatment regimen adherence is a significant factor in ARV success URMC-099's abilities to stimulate autophagy and extend ART actions may facilitate its use as a booster for regimens of long-acting ARVs.